Lower‐limb muscle function during gait in varus mal‐aligned osteoarthritis patients. Issue 8 (23rd March 2018) - Sritharan, Prasanna; Lin, Yi‐Chung; Richardson, Sara E.; Crossley, Kay M.; Birmingham, Trevor B.; Pandy, Marcus G.
ABSTRACT: This study quantified the contributions by muscular, gravitational and inertial forces to the ground reaction force (GRF) and external knee adduction moment (EKAM) for knee osteoarthritis (OA) patients and controls walking at similar speeds. Gait data for 39 varus mal‐aligned medial knee OA patients and 15 controls were input into musculoskeletal models to calculate the contributions of individual muscles and gravity to the fore‐aft (progression), vertical (support), and mediolateral (balance) GRF, and the EKAM. The temporal patterns of contributions to GRF and EKAM were similar between the groups. Magnitude differences in GRF contributions were small but some reached significance. Peak GRF contributions were lower in patients except hamstrings in early‐stance progression ( p  < 0.001) and gastrocnemius in late‐stance progression ( p  < 0.001). Both EKAM peaks were higher in patients, due mainly to greater adduction contribution from gravity ( p  < 0.001) at the first peak, and lower abduction contributions from soleus ( p  < 0.001) and gastrocnemius ( p  < 0.001) at the second peak. Gluteus medius contributed most to EKAM in both groups, but was higher in patients during mid‐stance only ( p  < 0.001). Differences in GRF contributions were attributed to altered quadriceps‐hamstrings action as well as compensatory adaptation of the ankle plantarflexors to reduced gluteus medius action. The large effect of varus mal‐alignment on the frontal‐plane moment arms of the gravity, soleus, and gastrocnemius GRF contributions about the knee explained greater patient EKAM. Our results shed further light on how the EKAM contributes to altered knee‐joint loads in OA and why some interventions may affect different portions of the EKAM waveform. © 2018 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:2157–2166, 2018.